Analisis Pengaruh Penerapan Green Banking dan Efisiensi Biaya Operasional terhadap Profitabilitas Bank Umum Syariah di Indonesia - Salma Nabila Mustika; Kristianingsih Kristianingsih; Fifi Afiyanti Tripuspitorini; Tjetjep Djuwarsa (Journal of Applied Islamic Economics and Finance, 2023)
The purpose of this study is to determine whether the implementation of green banking and operational cost efficiency can affect the profitability of Sharia Commercial Banks in 2016-2020. The variables used in this study are indicators of green banking as an exogeneous variables, BOPO as an intervening variable, and ROA as an endogenous. The type of data used in this study is secondary data in the form of panel data sourced from the annual reports of each Sharia Commercial Bank registered with the Financial Services Authority (OJK) in 2016-2020. Hypothesis testing is done by using a path analysis model. The results indicate that the implementation of green banking has a negative and significant effect on BOPO and has no direct effect on ROA of Sharia Commercial Banks. While, BOPO has negative and significant effect on ROA of Sharia Commercial Banks.